Cystoisospora suis – A Model of Mammalian Cystoisosporosis - Shrestha, Aruna; Abd-Elfattah, Ahmed; Freudenschuss, Barbara; Hinney, Barbara; Palmieri, Nicola; Ruttkowski, Bärbel; Joachim, Anja (Frontiers in Veterinary Science, 2015)
Cystoisospora suis is a coccidian species that typically affects suckling piglets. Infections occur by oral uptake of oocysts and are characterized by non-hemorrhagic transient diarrhea resulting in poor weight gain. Apparently, primary immune responses to C. suis cannot readily be mounted by neonates which contributes to the establishment and rapid development of the parasite, while in older pigs age-resistance prevents disease development. However, the presence of extraintestinal stages, although not unequivocally demonstrated, is suspected to enable parasite persistence together with the induction and maintenance of immune response in older pigs, which in turn may facilitate the transfer of C. suis-specific factors from sow to offspring. It is assumed that neonates are particularly prone to clinical disease because infections with C. suis interfere with the establishment of the gut microbiome. Clostridia have been especially inferred to profit from the altered intestinal environment during parasite infection. New tools, particularly in the area of genomics, might illustrate the interactions between C. suis and its host and pave the way for the development of new control methods not only for porcine cystoisosporosis but also for other mammalian Cystoisospora infections. The first reference genome for C. suis is under way and will be a fertile ground to discover new drugs and vaccines. At the same time, the establishment and refinement of an in vivo model and an in vitro culture system, supporting the complete life cycle of C. suis, will underpin the functional characterization of the parasite and shed light on its biology and control. Keywords: swine, piglets, Cystoisospora suis, immunology, microbiome, coccidian